2019
DOI: 10.1155/2019/8259645
|View full text |Cite
|
Sign up to set email alerts
|

Low-Energy Extracorporeal Shock Wave Therapy Ameliorates Kidney Function in Diabetic Nephropathy

Abstract: Background. Diabetic nephropathy is the most common cause of end-stage renal disease. Traditional therapy for diabetic nephropathy has focused on supportive treatment, and there is no significant effective therapy. We investigated the effect of low-energy extracorporeal shock wave therapy on a diabetic nephropathy rat model. Methods. Streptozotocin-induced diabetic nephropathy rats were treated with six sessions of low-energy extracorporeal shock wave therapy (weekly for six consecutive weeks) or left untreate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
66
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(68 citation statements)
references
References 35 publications
1
66
1
Order By: Relevance
“…This study showed that low-energy SW increased anti-inflammatory M2 macrophages. Low-energy SW is also reported to enhance anti-inflammatory M2 macrophage infiltration in a rat model of diabetic nephropathy [17] as well as acute myocardial infarction [24]. Low-energy SW might inhibit inflammation by polarizing pro-inflammatory M1 macrophages to anti-inflammatory M2 macrophages.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This study showed that low-energy SW increased anti-inflammatory M2 macrophages. Low-energy SW is also reported to enhance anti-inflammatory M2 macrophage infiltration in a rat model of diabetic nephropathy [17] as well as acute myocardial infarction [24]. Low-energy SW might inhibit inflammation by polarizing pro-inflammatory M1 macrophages to anti-inflammatory M2 macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Low-energy SW might inhibit inflammation by polarizing pro-inflammatory M1 macrophages to anti-inflammatory M2 macrophages. Low-energy SW has an anti-inflammatory effect against various diseases [17,29,33].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, several studies have shown that DPP4 inhibitors improve oxidative stress and protect against mitochondrial membrane depolarization in diabetic patients and diabetic rats 23,24 . Other studies suggest that DPP4 inhibition contributes to diabetic kidney protection partly through SDF‐1α‐dependent antioxidative and antifibrotic effects and through the amelioration of adverse renal hemodynamic 25,26 . Conversely, blockade of SDF‐1α/CXCR4 signaling with the antagonist AMD3100 in diabetic mice accelerates renal functional deterioration and aggravates glomerular hypertension 25 .…”
Section: Introductionmentioning
confidence: 99%